2013
DOI: 10.1186/1472-698x-13-41
|View full text |Cite
|
Sign up to set email alerts
|

The transition of childbirth practices among tribal women in Gujarat, India - a grounded theory approach

Abstract: BackgroundUnder the National Rural Health Mission, the current emphasis is on achieving universal institutional births through incentive schemes as part of reforms related to childbirth in India. There has been rapid progress in achieving this goal. To understand the choices made as well as practices and perceptions related to childbirth amongst tribal women in Gujarat and how these have been influenced by modernity in general and modernity brought in through maternal health policies.MethodA model depicting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…A review of Indian studies reveals only one qualitative study that mentions this malpractice [44]. However, other qualitative studies have reported that pain levels during labour and childbirth were considered to be ‘good’ by the Indian respondents [35,36,44]. To the best of our knowledge, no Indian study has yet explored the association between perineal wound suturing without local anaesthesia and birth satisfaction; however, our data show an association between perineal suturing without local anaesthesia and fear of childbirth [53], which in turn influences satisfaction with childbirth services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of Indian studies reveals only one qualitative study that mentions this malpractice [44]. However, other qualitative studies have reported that pain levels during labour and childbirth were considered to be ‘good’ by the Indian respondents [35,36,44]. To the best of our knowledge, no Indian study has yet explored the association between perineal wound suturing without local anaesthesia and birth satisfaction; however, our data show an association between perineal suturing without local anaesthesia and fear of childbirth [53], which in turn influences satisfaction with childbirth services.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-front promotion of institutional childbirths by the Government of India has resulted in an exponentially increasing number of women coming to hospitals with the chief expectation of ensuring the safety of themselves and their neonates [3538]. However, the expansion in the number of labour rooms and necessary resources and infrastructure, especially in public health facilities, has not been proportional to rising demand [36,39,40]. Labour rooms have become crowded and understaffed and face shortages of equipment and material [17,40] and the documentation processes around childbirth have been described to be ‘too much to do concurrently with actual care provision’, with care providers relying on verbal communication rather than maintaining written documentation of decision-making around childbirth [17,41].…”
Section: Introductionmentioning
confidence: 99%
“…However, as documented in a recent systematic review [20], what matters to women during childbirth is still relatively poorly documented. Specifically, among 35 studies identified by the systematic review [20], all had a very small sample (ie, maximum 35 women), with the only exception being a study in Sweden (908 women), one in Australia (202 women), and one in India (85 women) [21][22][23]. Additionally, these studies did not documented suggestions of women, collected after delivery, on how to improve QMNC, but rather expectations before delivery [21,22] or changes in cultural belief through generations [23].…”
Section: Introductionmentioning
confidence: 99%
“…17 The health system needs to find innovative and effective ways to strengthen midwifery and ensure the availability of and accessibility to safe delivery practices at community level. 18…”
Section: Discussionmentioning
confidence: 99%